Fire Protection in Various Types of Wooden Structures - Gašpercová Stanislava; Makovická Osvaldová Linda (Civil and Environmental Engineering, 2015)
Design of new modern systems for low energy efficient construction in a passive, zero standard or energy-autonomous buildings, as well as the increased popularity of solid wood construction means intervention into the very structure of its statics, building physics, but also fire properties. Some prototype design solutions are not verified whether the tests, by good computational analysis or verification of long-term use of the building. In the context of changing standards in building design, new approaches are needed. If in wooden buildings the potential risk of fire is higher than other buildings, we need special methods, materials and practical skills.